Family changes and the willingness to take risks - Mark J. Browne; Verena Jäger; Andreas Richter; Petra Steinorth (Journal of Risk and Insurance, 2022)
Economic decisions frequently entail choices in the presence of risk. Decisions to purchase insurance, to save, to invest, and to pursue an education are all choices that may involve some degree of risk, just to name a few. We analyze the impact of changes in family structure on individuals' willingness to take risk (WTR). We find evidence that separating from a partner is associated with an increase in the WTR; while the birth of a first child is associated with a decrease in the WTR. Interestingly, these changes are temporary and the WTR returns to the level observed before the family event within 1–2 years following the event. Married individuals are more risk averse and this does not change with the passage of time of the actual wedding. Providing long term care is also associated with a higher WTR.
Keywords: 330; family structure; marital status transitions; marriage; variable risk attitudes; willingness to take risks